In Vivo Importance of Actin Nucleotide Exchange Catalyzed by Profilin - Wolven, Amy K. (The Rockefeller University Press, 2000)
The actin monomer-binding protein, profilin, influences the dynamics of actin filaments in vitro by suppressing nucleation, enhancing nucleotide exchange on actin, and promoting barbed-end assembly. Profilin may also link signaling pathways to actin cytoskeleton organization by binding to the phosphoinositide PIP(2) and to polyproline stretches on several proteins. Although activities of profilin have been studied extensively in vitro, the significance of each of these activities in vivo needs to be tested. To study profilin function, we extensively mutagenized the Saccharomyces cerevisiae profilin gene (PFY1) and examined the consequences of specific point mutations on growth and actin organization. The actin-binding region of profilin was shown to be critical in vivo. act1-157, an actin mutant with an increased intrinsic rate of nucleotide exchange, suppressed defects in actin organization, cell growth, and fluid-phase endocytosis of pfy1-4, a profilin mutant defective in actin binding. In reactions containing actin, profilin, and cofilin, profilin was required for fast rates of actin filament turnover. However, Act1-157p circumvented the requirement for profilin. Based on the results of these studies, we conclude that in living cells profilin promotes rapid actin dynamics by regenerating ATP actin from ADP actin–cofilin generated during filament disassembly.